Annual Report of Recorded Phone Calls to Iran's Drug and Poison Information Centers (2014-2015) - Talat Ghane; Yasna Behmanesh; Fardin Khazaei (Asia Pacific Journal of Medical Toxicology, 2015)
Background: The annual statistics of Drug and Poison Information Centers (DPICs) have critical role in public health planning. The objective of this study was to provide annual epidemiologic profile of drug inquiry and poisoning-related phone calls to Iran’s DPICs during 2014-2015. Methods: This was a descriptive retrospective study by reviewing reported phone calls of Iranian DPICs to central division in Tehran (NDPIC) during one Iranian solar year (1393 A.H. equivalent to March 20th 2014 to 20th March 2015 A.D). Results: During the study period, 250368 phone calls were registered in 36 DPICs across the country. The majority of callers were women (145917, 58.28%). The most frequent calls were made by the individuals in the age group of 31 to 40 years (48795, 19.49%). Most of the calls were made by the patients (134322, 53.64%) followed by patients’ relatives (105646, 42.2%). The most common subject of calls was adverse drug reactions (42682, 19.4%), followed by therapeutic use (37114, 16.9%) and drug administration (30091, 13.7%) inquiries. Micromedex (54324, 21.70%) was the most commonly used reference to answer the inquiries. Given that 223482 calls were related to drug information inquiries, the most common drugs questioned about were antibiotics (24274, 10.86%); whereas 4548 calls were made about poisonings and the majority of them were due to pharmaceutical agents (2556, 56.20%). Conclusion: Iranian people seems to have numerous unmet drug information needs. This may especially be the case for antibiotics, nutrients and anti-depressants. Pharmaceutical products are the main subjects of poisoning-related calls to DPICs in Iran. Public education on usage, safety and storage of drugs as well as strict terms of sale should be implemented.